Electrical and thermal phenomena in low‐density polyethylene/carbon black composites near the percolation threshold. Issue 6 (20th August 2018) - Azizi, Sohrab; David, Eric; Fréchette, Michel F.; Nguyen‐Tri, Phuong; Ouellet‐Plamondon, Claudiane M.
ABSTRACT: Low‐density polyethylene (LDPE)/carbon black (CB) composites were fabricated via melt‐compounding technique. The percolation threshold was found to be around 20 wt % CB, and an electrical network formed by conductive CB was proven by scanning electron microscopy investigation. Dielectric responses depicted an interfacial relaxation peak at 20 wt % CB content. LDPE/CB composites showed an electric field‐dependent conductivity as and a hysteresis behavior around the percolation threshold region. The CB particles with high thermal conductivity increased the heat conductance of the LDPE/CB20 up to 56%. The dynamic mechanical analysis of the LDPE/CB composites exhibited a noticeable contribution of CB throughout the composites, increasing the storage and loss modulus. The physical interactions between CB particles in the filler network enhanced the thermal degradation of the LDPE/CB25 composite for more than 76°C. The maximum breakdown strength of the LDPE/CB composites appeared with an approximately 10% improvement for LDPE/CB5 than pure LDPE. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47043. Abstract :